Yā 'Ibādī method: Innovating Islamic education curriculum towards ma'rifatullāh (divine knowledge) in the digital age - Sholichah, Nikmatus; Taufani, Hudiyanti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
In the digital era, effectiveness and flexibility are paramount. Digital technology offers convenience in all aspects of life, including the ease of both obedience and disobedience, depending on the user's personal abilities. This paper aims to explore, theorize, and demonstrate that the Yā 'Ibādī method—an innovative approach to ma'rifatullah (divine knowledge)—is practical, beneficial, and can serve as a foundational, applicative, preventive, curative, and constructive solution towards ma'rifatullāh in the digital age. Utilizing qualitative grounded theory research, this study finds that the Yā 'Ibādī method employs Qur'anic verses as its educational medium, emphasizing a spiritual journey towards ma'rifatullāh through understanding, tadabbur (contemplation), and the application of explicit and implicit themes in the Qur'an to navigate daily life's challenges. The Yā 'Ibādī method can be incorporated into the Islamic education curriculum as a pathway to ma'rifatullāh in the digital era. It provides ordinary believers with a means to experience 'seeing' and 'being seen' by Allah SWT through their hearts, anytime and anywhere. This spiritual practice is facilitated by Allah's guidance in fostering obedience, protecting from disobedience, and enabling believers to navigate the digital age with peace, joy, and security. By grounding its teachings in the Qur'an, the Yā 'Ibādī method offers a comprehensive framework for spiritual growth and resilience, ensuring that individuals can live faithfully and confidently amidst the complexities of modern life. This integration of traditional spiritual practices with contemporary digital conveniences highlights the method's adaptability and relevance, promoting a balanced and fulfilling approach to faith in the 21st-century.